2018
DOI: 10.1159/000493524
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence Prognosis and Risk Factors of Cognitive Impairment in Maintenance Haemodialysis Patients

Abstract: Objective: To investigate the incidence and the prognosis of cognitive impairment (CI) and to find out the risk factors associated with the outcome in maintenance haemodialysis (MHD) patients. Methods: Enrolled the patients who met the criteria as below: MHD (≥3 months) patients before July 2014, ≥18 years old and could carry on the cognitive function test (Montreal Cognitive Assessment [MoCA]). All enrolled patients were divided into 2 groups: CI group (MoCA < 26) and non-CI group (MoCA ≥26). All patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 29 publications
3
39
1
Order By: Relevance
“…11 The prevalence of cognitive impairment in CKD patients ranges from 17% to 87% depending on severity. [12][13][14][15][16] Its prevalence among CKD patients is 20% in the United Kingdom, 17 75.5% in China, 18 and 53.8% in India. 19 A comparative cross-sectional study in Nigeria showed that the prevalence of cognitive impairment CKD patients is 35.3% whereas for the control group it is 6%.…”
Section: Introductionmentioning
confidence: 99%
“…11 The prevalence of cognitive impairment in CKD patients ranges from 17% to 87% depending on severity. [12][13][14][15][16] Its prevalence among CKD patients is 20% in the United Kingdom, 17 75.5% in China, 18 and 53.8% in India. 19 A comparative cross-sectional study in Nigeria showed that the prevalence of cognitive impairment CKD patients is 35.3% whereas for the control group it is 6%.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the survival rate of MHD patients with CI was signi cantly lower than that of patients with normal cognitive function, suggesting that CI is a risk factor for death of MHD patients [4] .…”
Section: Discussionmentioning
confidence: 96%
“…MoCA score which has been con rmed in the previous literature [5,6] was used to determine cognitive impairment in MHD patients in this study. Furthermore, the 3-year survival rate of MHD patients with CI was signi cantly lower than that of patients with normal cognitive function [4] .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Cognitive Impairment (CI) is one of the common neurological complications in patients with ESRD [3] . Our previous single-center cohort observational study showed that the incidence of CI in patients with maintenance hemodialysis (MHD) was 51.6% and 3 times higher than that of non-Kidney disease patients [4] . The 3-year survival rate of MHD patients with CI was signi cantly lower than that of patients with normal cognitive function [4] .…”
Section: Introductionmentioning
confidence: 99%